Inhibitory effects of protein kinase C inhibitor and calmodulin antagonist on tumor necrosis factor production by mouse macrophages - Tian Ming; Zhang Jun-Ping; Qian Ding-Hua; Li Guang-Chuan (Acta Pharmacologica Sinica, 2016)
Mouse peritoneal macrophages were primed with calcium ionophore calcimycin 1 mumol.L-1 for 8 h and then elicited by lipopolysaccharides (LPS, 10 ng.ml-1) for 6 h to induce tumor necrosis factor (TNF), measured by crystal violet staining assay using murine fibroblast L929 cells. Protein kinase C (PKC) inhibitor, 1-(5-isoquinolinesulphonyl)-2-methylpiperazine (H-7) and calmodulin (CaM) antagonist, N-(6-aminohexyl)-5-chloro-1-naphthalenesulfonamide (W-7) were studied on LPS-induced TNF production by macrophages. Addition of H-7 (0.31-50 micrograms.ml-1) and W-7 (10-4000 ng.ml-1) simultaneously with LPS to the culture medium suppressed LPS-induced TNF production in a concentration-dependent manner. When macrophages were pretreated with W-7 (10 ng.ml-1), LPS-induced TNF production was completely inhibited at 8 h. These results suggest that TNF production by macrophages may be dependent on the PKC and CaM.